(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate the bacterial characteristics and antibiotic resistance patterns in the Intensive Care Unit of Children’s Hospital 2 Methods: A retrospective, cross-sectional descriptive study was conducted, collecting data from 946 clinical specimens of 350 pediatric patients treated in the ICU between June 2022 and June 2023. Results: The overall positive culture rate was 26.8%, with Gram-negative bacteria accounting for 86.6% of isolates. The most frequently identified pathogens were Acinetobacter baumannii (26.4%), Klebsiella pneumoniae (22.0%), and Pseudomonas aeruginosa (13.8%). Susceptibility to broad-spectrum antibiotics, particularly carbapenems, was notably low for A. baumannii and K. pneumoniae. Colistin exhibited the highest efficacy against A. baumannii (80.6%) and P. aeruginosa (97.1%) but demonstrated a reduced susceptibility rate of 32.1% for K. pneumoniae. The prevalence of multidrug-resistant (MDR), extensively drug-resistant (XDR), and pan-drug-resistant (PDR) isolates was 34.3%, 28.7%, and 8.3%, respectively. Conclusion: The study highlights a high prevalence of antimicrobial resistance among bacterial pathogens, particularly A. baumannii and K. pneumoniae. Surveillance and optimization of antibiotic regimens are essential to control resistance.